Unusual dynamic precipitation softening induced by dislocation glide in biomedical beta-titanium alloys - Koji Hagihara; Takayoshi Nakano; Mitsuharu Todai (Scientific Reports, 2017)
Abstract Softening of metallic materials containing precipitates during cyclic deformation occurs through dissolution of the precipitates, because the to-and-fro motion of the dislocation causes dissolution of the precipitate particles by cutting them. Here, however, we found the completely opposite phenomenon for the first time; a “dynamic precipitation softening” phenomenon. In a Ti-35Nb-10Ta-5Zr body-centered cubic structured β-Ti alloy single crystal developed for biomedical implant, the to-and-fro motion of the dislocation “induced” the selective precipitation of the ω-phase whose c-axis is parallel to the Burgers vector of the moving dislocation, which led to the significant cyclic softening of the crystal. The formation of the ω-phase is generally believed to induce significant hardening of β-Ti alloys. However, the present results suggest that this is not always true, and control of the anisotropic features of the ω-phase via control of crystal orientation can induce unusual mechanical properties in β-Ti alloys. The unique anisotropic mechanical properties obtained by the cyclic-deformation-induced oriented ω-phase formation could be useful for the development of “single-crystalline β-Ti implant materials” with advanced mechanical performance.